2023
DOI: 10.1101/2023.02.01.526349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RGS14 is neuroprotective against seizure-induced mitochondrial oxidative stress and pathology in hippocampus

Abstract: RGS14 is a complex multifunctional scaffolding protein that is highly enriched within pyramidal cells (PCs) of hippocampal area CA2. There, RGS14 suppresses glutamate-induced calcium influx and related G protein and ERK signaling in dendritic spines to restrain postsynaptic signaling and plasticity. Previous findings show that, unlike PCs of hippocampal areas CA1 and CA3, CA2 PCs are resistant to a number of neurological insults, including degeneration caused by temporal lobe epilepsy (TLE). While RGS14 is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…RGS14 is known to suppress long-term potentiation and is required for long-term depression in hippocampal field CA2 (Evans et al, 2018b; Lee et al, 2010; Samadi et al, 2023). Our group has also recently shown that RGS14 protein expression can be markedly upregulated in the hippocampus as a protective mechanism in response to seizure-induced hyperactivity (Harbin et al, 2023). Considering that many RGS14-containing regions identified in this report are known to be conditionally plastic, it is possible that RGS14 functions as a tunable regulator of synaptic plasticity throughout many functionally related parts of the rodent brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS14 is known to suppress long-term potentiation and is required for long-term depression in hippocampal field CA2 (Evans et al, 2018b; Lee et al, 2010; Samadi et al, 2023). Our group has also recently shown that RGS14 protein expression can be markedly upregulated in the hippocampus as a protective mechanism in response to seizure-induced hyperactivity (Harbin et al, 2023). Considering that many RGS14-containing regions identified in this report are known to be conditionally plastic, it is possible that RGS14 functions as a tunable regulator of synaptic plasticity throughout many functionally related parts of the rodent brain.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is a strong driver of experience-based neuroplasticity, and RGS14 likely works to keep its influence in check (Speranza et al, 2021). While speculative, it is possible that RGS14 could even be induced in response to dopaminedriven hyperexcitation, similar to that which is seen during status epilepticus (Harbin et al, 2023).…”
Section: Overview Of Rgs14 Expression In Mouse Brainmentioning
confidence: 99%
“…7 Harbin et al recently evaluated the impact of changes in RGS14 in the CA2 region in a mouse seizure model. 8 Their findings provide further insight into how RGS14 regulates hyperexcitability in the hippocampus. In addition, these studies shed light on the role of the CA2 region that has been relatively understudied for its role in epilepsy.…”
Section: Commentarymentioning
confidence: 90%